2016
DOI: 10.3168/jds.2015-9884
|View full text |Cite
|
Sign up to set email alerts
|

Straw particle size in calf starters: Effects on digestive system development and rumen fermentation

Abstract: Two trials were conducted to determine effects of straw particle size in calf starter on rumen fermentation and development in calves. Holstein calves (n=17 in trial 1; n=25 in trial 2) were housed in individual pens; bedding (wood shavings) was covered with landscape fabric to completely avoid consumption of bedding. Milk replacer was fed at 12% of birth body weight per day and water offered free choice. Calves were randomly assigned to 4 treatments differing in geometric mean particle length (Xgm) of straw c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
2
33
0
2
Order By: Relevance
“…Longer particle size improved performance [8], probably because of the increased rumination time of calves, which increased saliva production, and consequently improved buffering effect on the ruminal environment [63,64]. However, inconsistent results have been obtained by Omidi-Mirzaei [65] and Suárez-Mena [66]. Omidi-Mirzaei et al [65] reported that when calves were fed forage with different particle size (alfalfa hay: short = 1.96 mm or long = 3.93 mm; and wheat straw: short = 2.03 mm or long = 4.10 mm as geometric mean), rumination time increased in calves fed forage with long particle size, but concentrate DMI, ADG, and FE were not affected.…”
Section: Forage Physical Forms and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer particle size improved performance [8], probably because of the increased rumination time of calves, which increased saliva production, and consequently improved buffering effect on the ruminal environment [63,64]. However, inconsistent results have been obtained by Omidi-Mirzaei [65] and Suárez-Mena [66]. Omidi-Mirzaei et al [65] reported that when calves were fed forage with different particle size (alfalfa hay: short = 1.96 mm or long = 3.93 mm; and wheat straw: short = 2.03 mm or long = 4.10 mm as geometric mean), rumination time increased in calves fed forage with long particle size, but concentrate DMI, ADG, and FE were not affected.…”
Section: Forage Physical Forms and Processingmentioning
confidence: 99%
“…Omidi-Mirzaei et al [65] reported that when calves were fed forage with different particle size (alfalfa hay: short = 1.96 mm or long = 3.93 mm; and wheat straw: short = 2.03 mm or long = 4.10 mm as geometric mean), rumination time increased in calves fed forage with long particle size, but concentrate DMI, ADG, and FE were not affected. Suárez-Mena et al [66] compared four different particle sizes (0.82, 3.04, 7.10, and 12.7 mm as geometric mean) of low-quality forage (5% straw) mixed in the diet and observed no effect on DMI, growth performance, and minimal changes in rumen fermentation and pH among treatments. In summary, these results imply that interactions may exist among forage source, level, and particle size, and the optimal inclusion level of forage should be determined based on the forage source and particle size.…”
Section: Forage Physical Forms and Processingmentioning
confidence: 99%
“…This can be achieved using a feeding regimen aimed at early rumen development (ERD), which includes feeding both roughage and concentrate from an early age onward. An increase in rumen volume and weight is stimulated by the feeding of fibrous feeds, whereas the development of rumen papillae is stimulated by volatile fatty acids and therefore by less fibrous feeds Suarez-Mena et al, 2016).…”
Section: Rumen Developmentmentioning
confidence: 99%
“…The VFAs that are products of the fermentation of diets are essential to the rumen papillae development and nutrient source for host requirements (15). In ruminants, VFA produced in the rumen meets 70–80% of the energy requirement for the rumen epithelia, and 50–70% of the energy requirement for the body (16).…”
Section: Discussionmentioning
confidence: 99%